Pijat Tui Na Untuk Meningkatkan Berat Badan Balita Di TPMB Intan Pratiwi Tahun 2023 - Pratiwi, Intan; Simanjuntak, Herlina (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Tui Na massage is a more specific massage technique for overcoming feeding difficulties in toddlers by improving blood circulation in the spleen and digestion. Tui Na massage is a more specific massage technique for overcoming feeding difficulties in toddlers by improving blood circulation in the spleen and digestion, through a modification of acupuncture without needles, this technique uses pressure on the body's meridian points or energy flow lines so it is relatively easier to do. compared to acupuncture, the aim of the research was to determine the effect of Tui Na massage on weight gain in toddlers at TPMB Intan Pratiwi, Cikampek Karawang District in 2023. This design is a quasi-experimental research with a one group pretest-posttest design. The population of this study was 45 toddlers, where the research was conducted at TPMB Intan Pratiwi, Cikampek District, Karawang Regency in 2023 on October 15 – November 15. The research sample consisted of 31 respondents, with sample collection through purposive sampling. The dependent variable is body weight. The independent variable is Tui Na massage. The results of univariate analysis using frequency distribution in the form of percentages, average values, bivariate analysis using Paired Sample T-Test obtained a Sig (2-tailed) value of 0.001<0.005, which means that there is an effect of Tui Na massage on weight gain in toddlers at TPMB Intan Pratiwi, Cikampek Karawang District in 2023.The conclusion from this research is that there is an effect of Tui Na massage on the weight gain of toddlers